First principles investigation of elastic, electronic and thermoelectric properties of lead-free Cs–X–I (X = Pb, Gd, Nd, Y) perovskites - Adel Bandar Alruqi; Nicholas O Ongwen (Journal of Physics Communications)
Perovskites have become the center of recent research for their possible application in perovskite solar cells, owing to their desirable optical and electronic properties, flexibility, tunability, and low–cost fabrication. Most of the perovskites are however made of lead, which is a highly poisonous element. It is therefore necessary to seek alternative perovskites for this application that are less toxic. This study investigated the elastic, electronic, and thermoelectric properties of Cs–X–I (X = Pb, Gd, Nd, and Y) as possible replacements to the leaded CsPbI _3 due to their less toxic nature. The density functional theory was utilized in the computations, with quantum espresso and BoltzTrap packages. The results showed that all the materials were structurally stable. The computed mechanical properties also showed that all the other materials had better elastic constants compared to those of CsPbI _3 . CsPbI _3 was observed to exhibit the lowest band gap, unlike the others. Moreover, the other materials possessed higher elastic constants, electrical conductivities, and lowest thermal conductivities, which are highly needed in the perovskite solar cells. However, an experimental treatment needs to be done on the studied structures in order to confirm the properties obtained in this work.